Knowledge, Attitudes, and Safety Practices About COVID-19 Among High School Students in Iran During the First Wave of the Pandemic - Hossein Hatami; Mohsen Abbasi-Kangevari; Mohammad-Reza Malekpour; Ali-Asghar Kolahi (Frontiers Media S.A., 2021)
Background: School closures have inevitably deprived students of their traditional source of information. The objective of this study was to determine knowledge, attitudes, and safety practices about COVID-19 among high school students in Iran.Methods: This study was conducted from March 24th-April 3rd, 2020. Data were collected via an online-parent-administrative questionnaire.Results: Responses of 704 students were analyzed. Students' mean (SD) knowledge score was 21.5 (4.6) of 30. More than 90% of students knew about the cause of the disease, the routes of transmission, and the most renowned symptoms: dyspnea and cough. Social-and- audiovisual-media were the leading information source. Most students believed that people need to keep safe physical distancing, everyone should isolate themselves upon symptoms onset, people should avoid unnecessary in-person contact with family and friends, and that cities need to go under lockdowns if needed. Students' mean (SD) practice score was 20.2 (2.5) of 24. Most students did not go on a trip, and more than 80% said they would wear facemasks when going outside.Conclusions: High school students' knowledge and safety practices about COVID-19 were somewhat satisfactory, and their attitudes toward the disease were mainly positive. Nevertheless, some witnessed knowledge gaps, negative attitudes, and unsafe practices in the study highlighted the need for targeted education on the pandemic. Social and mass media's significant role and potential could be utilized to battle misinformation and deliver proper knowledge to young adolescents.